Bibliographic control of audiovisuals: analysis of a cataloging project using OCLC. - Curtis, J A (1985)
The staff of the Quillen-Dishner College of Medicine Library cataloged 702 audiovisual titles between July 1, 1982, and June 30, 1983, using the OCLC database. This paper discusses the library's audiovisual collection and describes the method and scope of a study conducted during this project, the cataloging standards and conventions adopted, the assignment and use of NLM classification, the provision of summaries for programs, and the amount of staff time expended in cataloging typical items. An analysis of the use of OCLC for this project resulted in the following findings: the rate of successful searches for audiovisual copy was 82.4%; the error rate for records used was 41.9%; modifications were required in every record used; the Library of Congress and seven member institutions provided 62.8% of the records used. It was concluded that the effort to establish bibliographic control of audiovisuals is not widespread and that expanded and improved audiovisual cataloging by the Library of Congress and the National Library of Medicine would substantially contribute to that goal.